Bribery, insecurity, and firm performance: Evidence from the Boko Haram insurgency in Nigeria - Dimitriadis, Stefan (Strategic Management Journal, 2024)
Abstract Research Summary During armed conflicts, when the rule of law collapses, bribery often becomes prevalent. Yet, the effect of bribery on firm performance under those circumstances remains unclear. Bribery could provide access to scarce resources, but it could also be the result of extortion. This study argues that bribes can improve firm performance during certain conflicts, when violence reduces public officials' ability to threaten firms. Using longitudinal data from businesses in Nigeria during the Boko Haram insurgency in 2009–2014, I find that firms exposed to Boko Haram attacks that bribed outperformed firms that did not bribe. Qualitative data suggest that the insurgency limited public officials' ability to threaten firms, making bribes less a means of rent extraction and more a way for firms to access resources. Managerial Summary In many economies, bribery is widespread despite being illegal. This study shows that during times of violent conflict bribery can be a way for firms to maintain operations despite the disruption. Using data from firms in Nigeria during the 2009–2014 Boko Haram insurgency, I find that firms that bribed tended to suffer less from the effects of the insurgency. Bribing firms were better able to secure protection and access transportation networks. At the same time, the conflict reduced local officials' ability to extort firms, making bribes less likely to involve extortion. These results highlight the extreme circumstances that firms face during violent conflicts and the illicit practices that may enable them to survive in the short run.